Acceptability, feasibility, and user satisfaction of a virtual reality relaxation intervention in a psychiatric outpatient setting during the COVID-19 pandemic - Humbert, Annika; Kohls, Elisabeth; Baldofski, Sabrina; Epple, Carola; Rummel-Kluge, Christine (Frontiers in Psychiatry, 2023)
The COVID-19 pandemic was particularly difficult for individuals with mental disorders. Due to governmental restrictions, face-to-face offers for psychiatric outpatients like therapies, psychoeducational groups or relaxation courses were limited. Virtual reality (VR) might be a new possibility to support these patients by providing them with a home-based relaxation tool.The aim of this study was to evaluate the acceptability, feasibility, and user satisfaction of a supportive therapy-accompanying, relaxation VR intervention in psychiatric outpatients during the COVID-19 pandemic in Germany.The four-weeks VR intervention consisted of regular watching of relaxing videos in the participants' home environment. Sociodemographics, feasibility (frequency of use, userfriendliness), satisfaction (Client Satisfaction Questionnaire-8), depressive symptoms (Patient Health Questionnaire-9), quality of life (abbreviated World Health Organization Quality of Life assessment), and credibility and expectancy (Credibility Expectancy Questionnaire-8) were measured in an intention-to-treat (ITT) analysis and a per-protocol (PP) analysis of completers.In total, N = 40 patients participated in the study. Most of the participants in the ITT analysis (n = 30, 75.0%) used the VR device three or four weeks. A majority of the N = 29 completers (PP: n = 18, 62.1%) used it all four weeks. Most participants used the device two or more times a week (ITT: n = 30, 83.3%; PP: n = 26, 89.7%) and described the user-friendliness as rather or very easy (ITT: n = 33, 91.7%; PP: n = 26, 89.7%). User satisfaction was high (ITT: 19.42, SD = 4.08; PP: M = 20.00, SD = 4.19) and did not correlate with participants' sex or age (all p < .05). Depressive symptoms and psychological quality of life improved significantly from pre-to post-intervention (ITT and PP, all p < .05). Higher pre-intervention credibility significantly correlated with a better outcome of satisfaction (ITT and PP), depressive symptoms, physical, psychological, and social quality of life (PP; all p < .05).A supportive therapy-accompanying VR relaxation intervention is feasible and acceptable in a psychiatric outpatient setting. Due to the high satisfaction and user-friendliness, VR can be an easy to implement relaxation tool to support psychiatric outpatients.